Answer: -7, -5, -3, -1
Step-by-step explanation:
Using the below formula, the sequence can be determined:
aₙ = aₙ₋₁ + 2
The question/query does not explicitly specify the nth term to be identified. Hence, answering this question open-endedly.
aₙ is the nth term that needs to be identified
aₙ₋₁ is the term before aₙ
Based on the sequence -2, -3, -5, -9 from the question, a₁ = -2, a₂ = -3, a₃ = -5, a₄ = -9. Say, for example, we need to find the 8th term, then we need to find the 7th term first.
So, the sequence of order will be a₅, a₆, a₇, a₈
Now, each term is two more than the previous term
a₅ = a₄ + 2 = -9 + 2 = -7
a₆ = a₅ + 2 = -7 + 2 = -5
a₇ = a₆ + 2 = -5 + 2 = -3
a₈ = a₇ + 2 = -3 + 2 = -1